New species of Pseudonannolene Silvestri, 1895 from Brazilian limestone caves with comments on the potential distribution of the genus in South America (Spirostreptida: Pseudonannolenidae) - Iniesta, Luiz Felipe Moretti; Ferreira, Rodrigo Lopes (Zootaxa, 2014)
Ten new species of Pseudonannolene Silvestri, 1895 are described from Brazilian limestone caves. The species are separated by the morphology of their gonopods and the processes of the first pair of legs of males. A pictorial identification key for the cave-dwelling species from Brazil is provided, besides comments on the distribution of the genus with a potential distribution map of Pseudonannolene and Epinannolene in South and Central America.